Characterization of the in vitro, ex vivo, and in vivo Efficacy of the Antimicrobial Peptide DPK-060 Used for Topical Treatment - Håkansson, Joakim; Ringstad, Lovisa; Umerska, Anita; Johansson, Jenny; Andersson, Therese; Boge, Lukas; Rozenbaum, René T.; Sharma, Prashant K.; Tollbäck, Petter; Björn, Camilla; Saulnier, Patrick; Mahlapuu, Margit (Frontiers in Cellular and Infection Microbiology, 2019)
Antimicrobial peptides, also known as host defense peptides, have recently emerged as a promising new category of therapeutic agents for the treatment of infectious diseases. This study evaluated the preclinical in vitro, ex vivo, and in vivo antimicrobial activity, as well as the potential to cause skin irritation, of human kininogen-derived antimicrobial peptide DPK-060 in different formulations designed for topical delivery. We found that DPK-060 formulated in acetate buffer or poloxamer gel caused a marked reduction of bacterial counts of Staphylococcus aureus in vitro (minimum microbicidal concentration <5 μg/ml). We also found that DPK-060 in poloxamer gel significantly suppressed microbial survival in an ex vivo wound infection model using pig skin and in an in vivo mouse model of surgical site infection (≥99 or ≥94% reduction in bacterial counts was achieved with 1% DPK-060 at 4 h post-treatment, respectively). Encapsulation of DPK-060 in different types of lipid nanocapsules or cubosomes did not improve the bactericidal potential of the peptide under the applied test conditions. No reduction in cell viability was observed in response to administration of DPK-060 in any of the formulations tested. In conclusion, the present study confirms that DPK-060 has the potential to be an effective and safe drug candidate for the topical treatment of microbial infections; however, adsorption of the peptide to nanocarriers failed to show any additional benefits.